2015
DOI: 10.1186/s12877-015-0139-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring risk profiles and emergency frequency of purchasers and non-purchasers of personal emergency alarms: a prospective cohort study

Abstract: BackgroundPersonal alarms support independent living and have the potential to reduce serious consequences after a fall or during a medical emergency. While some Australian states have government funded personal alarm programs, others do not; but user-pays services are available. Although several studies have examined the profiles of alarm users, little is known about the risk profile of non-users. Specifically, whether there are “at risk” individuals who are unable, or choose not to purchase a service, who ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 17 publications
(30 reference statements)
2
17
0
Order By: Relevance
“…Regarding the numbers and types of emergencies experienced, there were no significant differences between the purchasers of the alarm system and non-purchasers [33]. Older adults used the alarm system as a strategy to maintain their independence and minimize the unexpected risks [38].…”
Section: Evidence Of Improving the Physical Mental And Social Wellbeingmentioning
confidence: 94%
See 3 more Smart Citations
“…Regarding the numbers and types of emergencies experienced, there were no significant differences between the purchasers of the alarm system and non-purchasers [33]. Older adults used the alarm system as a strategy to maintain their independence and minimize the unexpected risks [38].…”
Section: Evidence Of Improving the Physical Mental And Social Wellbeingmentioning
confidence: 94%
“…Using EAT may improve older adults' mental health. A significant difference in the incidence of depression was identified between the purchasers and non-purchasers of an alarm system, with more nonpurchasers suffering from depression [33].…”
Section: Evidence Of Improving the Physical Mental And Social Wellbeingmentioning
confidence: 98%
See 2 more Smart Citations
“…More recent research has explored the characteristics of users (De San Miguel et al, 2015;Nyman & Victor, 2014) and older people's perspectives on using personal alarms and reasons for nonuse (De San Miguel & Lewin, 2008;Heinbuchner, Hautzinger, Becker, & Pfeiffer, 2010;Johnston, Grimmers-Sommers, & Sutherland, 2010;Levine & Tideiksaar, 1995;Mann, Belchior, Tomita, & Kemp, 2005). While some of these studies have reported perceived benefits, there are still gaps in knowledge in terms of what impact an alarm has on particular health outcomes.…”
Section: Introductionmentioning
confidence: 99%